IJCM_92A: Pregnancy outcomes associated with antenatal care service utilization & barriers and enablers affecting the utilization of antenatal care services in South-East Delhi: A community-based cross-sectional study - Bano Aysha; Islam Farzana; Alvi Yasir (Wolters Kluwer Medknow Publications, 2024)
Background: Antenatal care provides preventive health care, through which women can learn from skilled health personnel. Women who don't consume Iron Folic Acid Supplements as prescribed would experience iron and folic acid (IFA) deficiency anemia. Iron deficiency has negative effects on mothers and newborns while folic acid deficiency in pregnancy causes pre-eclampsia, preterm delivery, neural tube defects, fetal malformation, type 2 diabetes, and obesity in the newborn. Comprehensive antenatal care is early registration of pregnancy (within 12 weeks), at least four ANC visits at a health facility, two doses of tetanus toxoid, and at least 100 days of IFAS consumption. Objectives: 1-To assess pregnancy outcomes associated with antenatal care service utilization in participants aged 18-49 years residing in the field practice areas of a Medical College in South-East Delhi. 2-To determine the barriers and enablers affecting the utilization of antenatal care services in the given population. Methodology: It is a community-based cross-sectional study conducted in South-East Delhi. The sample size was calculated as 300 considering a 5% absolute error for a 95% confidence interval and 10% non-response rate. Out of 300, the current data of 200 participants will be depicted here. Stratified systematic random sampling with the Probability Proportional to Size technique was applied to the population registered at RHTC & UHTC. Households were selected by systematic random sampling. Pregnant women aged between 18-49 years were selected from the household. A self-designed, pre-tested, validated structured questionnaire was used. Results: Out of the total number of participants, 66.0% had knowledge regarding early registration of pregnancy. 80.0 % had permission to attend a health facility, 70.5 % had an accompanying person, 62.5 % of participants had been residing more than 6 km away from the health facility. 58.0 % of participants could meet the expenses of health care services. Out of all newborns, 90.0 % had normal birth weights, 10% had low birth weights, 81.0% participants had NVDs, and 19% were caesarean sections. Conclusion: Enablers are knowledge regarding early registration, presence of accompanying person. Permission for health visits, expenses for health care services & distance to health facility were barriers.